MODERN MODELS OF ENSURING THE SECURITY OF INFORMATION SYSTEMS BASED ON ARTIFICIAL INTELLIGENCE IN THE CONDITIONS OF DIGITAL TRANSFORMATION (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the issue of ensuring the security of information systems based on artificial intelligence in the digital economy and e-government environment from a scientific, theoretical and practical perspective. The study examines the relationship between the classical principles of cybersecurity and the classification of risks for web applications and LLM applications in 2025, as well as new strategic and legal documents adopted in Uzbekistan. The article is based on the fact that cyber risks on a global scale lead to financial, organizational and institutional losses, and artificial intelligence is simultaneously a means of protection and a source of new risks. The author proposes a five-layer integrated security model of “information-model-infrastructure-human-management”. The results of the study show that in the context of the increasing pace of implementation of artificial intelligence in Uzbekistan, security should be viewed not only as a technical problem, but also as a complex issue related to legal, organizational, personnel policy and standardization. The article is intended for scientists, doctoral students, and practitioners conducting research in the fields of information technology, cybersecurity, and digital governance.